Evaluasi Kemampuan Lahan di Desa Sungai Jelayan Kecamatan Kedawangan Kabupaten Ketapang - Jainudin, Sani; Hazriani, Rini; Arief, Feira B.; Ridwansyah, Ridwansyah; Junaidi, Junaidi (Proceedings Series on Physical & Formal Sciences, 2021)
Sungai Jelayan Village is one of the villages in Kendawangan District, Ketapang Regency, which still has the potential for sustainable management. Evaluation of land capability is one of the efforts to overcome the reduction of land degradation. Land capability is an assessment of land units for particular uses, assessed from each inhibiting factor. This study aimed to determine the characteristics of the land according to the land capability parameter, assessed the land capability sub-class, and provided suggestions for land use based on the land capability sub-class in Sungai Jelayan Village. The research stages started from preparation, preliminary survey, determination of research location based on land units consisting of soil type, slope class, land use and there were 9 land units, and determination of observation points, as well as field observations and soil sampling, laboratory analysis, data processing and presentation of results. The results obtained 2 soil orders, namely Entisols and Inceptisols. The results of the land capability evaluation were divided into five land capability classes and sub-classes, namely class II-s, III-s, IV-w, V-w, and VIII-es. Improvement efforts or efforts to use land sustainably could be carried out in 5 ways, namely intensive cultivation, moderate cultivation, limited cultivation, nature reserves/protected forests, and intensive grazing.